(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article presents information on the role of risk in occupational safety management at industrial enterprises, a systematic approach to safety management, life cycle stages, and management functions. Methods for constructing activity decomposition based on systematic analysis and analyzing the “Cause and Risk Tree” system are covered.